Condition of creative writing in the North and South Punjab - Jawed Hassaan Chandio; Hafiz Muhammad Ather Khan; Muhammad Samiullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
Creative writing has an important place in the educational institutions. It is ignored in Pakistani English Language Teaching (ELT) classrooms. This study was designed to investigate the condition of creative writing skills of 9th graders. This study had been started with the review of the literature; many studies were found which analyzed different aspects of creative writing in ELT classrooms. A need was felt to see the condition of the four levels of creative writing namely descriptive writing, narrative writing, story writing, and functional writing among the secondary school level students. A sample of 238 students was selected from North and South of the Punjab province of Pakistan. Six classes from govt. and private sector schools were the sample.The major objectives of the study were to explore the condition of the above mentioned levels of creative writing in teaching of English at secondary level. Four tasks for creative writing were adapted from the Cambridge University O-level examinations and were piloted at a smaller group. These tasks constituted the achievement test. The tests were marked qualitatively with the help of scoring rubrics by using the method of "analytic scoring". The scores in creative writing test were rechecked and verified by the concerned teachers for inter-rater reliability. The results of the study showed that the creative writing skills among the secondary school students are dissatisfactory. In the end it was recommended that teachers should use communicative approach while teaching English language in secondary level classrooms. It was also recommended that the examination papers should have some unseen tasks to enhance the creative writing skills of secondary school students.
Keywords: 330; Creative writing; English language teaching; communicative approach